2022
DOI: 10.1021/acs.iecr.2c01418
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide-Based Electronanofiltration Membranes for Efficient Anion Separation

Abstract: Monovalent anion (i.e., Cl–/SO4 2–) permselective membranes with high permselectivity, low cost, and excellent stability are urgently desired in the chlor-alkali industry. Herein, a facile interfacial polymerization strategy is employed to fabricate polyamide-based electronanofiltration (ENF) membranes for efficient anion separation. The densely cross-linked network structure and the strong electrostatic repulsion to anions of high valence by a high density of carboxylic residuals lead to the low permeation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, electrodialysis with a nanofiltration membrane (EDNF) showed promising results for improving the demineralization rate [ 81 , 88 ] and acid recovery [ 88 ]. The technology was tested for the separation of cations and anions and demonstrated a high potential for applications in the chloralkali industry [ 88 , 89 , 90 ] or for desalinization [ 81 , 88 ].…”
Section: Electromembrane Processes: General Aspectsmentioning
confidence: 99%
“…Moreover, electrodialysis with a nanofiltration membrane (EDNF) showed promising results for improving the demineralization rate [ 81 , 88 ] and acid recovery [ 88 ]. The technology was tested for the separation of cations and anions and demonstrated a high potential for applications in the chloralkali industry [ 88 , 89 , 90 ] or for desalinization [ 81 , 88 ].…”
Section: Electromembrane Processes: General Aspectsmentioning
confidence: 99%
“…Divalent ions are usually better rejected than monovalent ions by NFMs in pressure-driven filtration because of (1) weaker partition of divalent ions to the PA matrix due to stronger steric, dielectric, dehydration, and Donnan effects of divalent ions and (2) more severe hindered transport of divalent ions inside the membrane pores . For the specific application of Li/Mg separation, positively charged NFMs, fabricated via coating positively charged polymers on the surface or introducing positively charged monomer to the interfacial polymerization step, have a higher Li/Mg selectivity than regular NFMs as a result of the stronger Donnan exclusion to Mg 2+ . NFMs have been proposed to replace commercial monovalent selective CEMs in the ED process to enhance the monovalent/divalent ion selectivity and reduce the membrane cost. Even though the uncharged support layer in NFMs also allows anions to permeate through, which may reduce charge efficiency, studies have also shown that using NFMs in the ED process does not require a higher energy consumption as compared to that using commercial monovalent selective CEMs. …”
Section: Introductionmentioning
confidence: 99%
“…Due to their more open pore structure compared to reverse osmosis (RO) membranes, nanofiltration (NF) membranes have been used in various applications that require selective separation between solutes, such as water softening, groundwater purification, and concentration of products in certain industries. More recently, with a growing demand for more challenging separations that require precise selectivity (e.g., lithium recovery from salt-lake brines), NF membranes have become a leading candidate to pursue such selectivity. Relying on steric hindrance, Donnan (charge) exclusion, and other molecular mechanisms, NF membranes of different materials and fabrication approaches were proposed to create selectivity toward different solutes. ,, Although success has been abundantly reported, the selectivity of most NF membranes is relatively limited, unspecific, and, for comparison, a few orders of magnitude lower than the selectivity of ion-selective biological channels. …”
Section: Introductionmentioning
confidence: 99%